Transport properties of refractory high-entropy alloys with single-phase body-centered cubic structure. (1st July 2023) - Dong, Yaguang; Mu, Sai; Guo, Xun; Han, Junfeng; Duan, Junxi; Jia, Nannan; Xue, Yunfei; Jin, Ke
Abstract: The transport properties of a series of refractory high-entropy alloys (RHEAs) with single-phase body-centered cubic structures are investigated based on both experiments and first-principles calculations. The measured residual electrical resistivities are high in general and cover a wide range, from 35 to 100 μΩ⋅cm. As opposed to the broadly studied 3 d -transition-metal HEAs with face-centered cubic structures, in which chemical disorder plays the key role on transport properties, pronounced lattice distortion and its remarkable influence on residual resistivities are demonstrated here in RHEAs. Moreover, the temperature dependence of resistivity in RHEAs are systematically smaller than those in the 3 d -transition-metal HEAs at similar resistivity values. Furthermore, the compositional dependence of thermal conductivity is not fully in line with that of electrical conductivity, indicating different fraction of contributions from the lattice and electronic systems to the thermal transport. Graphical abstract: Image, graphical abstract